The Influence of Leasing Upon Wildlife Management and Hunting Opportunity - Michael D. Porter (National Quail Symposium Proceedings, 2017)
(Invited Paper) Leasing can stimulate better wildlife management on private land. Thus wildlife professionals should support leasing. Private landowners provide most hunting opportunity but receive a disproportionately small share of the revenue generated by hunting, Leasing is a just system that pays the person producing wildlife and charges the person using it, Leasing is not always detrimental to hunting opportunity. Considerations concerning the effect of leasing upon hunting opportunity are less important than considerations concerning the effect of leasing upon wildlife management.